Effectiveness of Postoperative Adjuvant Radiotherapy in Atypical Meningioma Patients After Gross Total Resection: A Meta-Analysis Study - He, Lingzhe; Zhang, Buyi; Zhang, Jianmin; Guo, Zhige; Shi, Feina; Zeng, Qiang (Frontiers in Oncology, 2021)
Background It still remains unclear whether patients with atypical meningioma (AM) could benefit from postoperative adjuvant radiotherapy (PORT) after gross-total resection (GTR). Objective Exploring the effectiveness of PORT on AM patients after GTR. Methods Literatures on PubMed, Embase, Web of science, and Scopus databases published between January 2000 and January 2019 were searched. After the selection based on the certain exclusion criteria, the Newcastle-Ottawa evaluation scale was used to evaluate the quality of the included literatures. Finally, a meta-analysis was conducted to analyze the effectiveness of PORT on local control (LC), progression-free survival (PFS) and overall survival (OS) in atypical meningioma patients after GTR. Results A total of 17 articles with 2,008 AM patients were included in the meta-analysis. The 5-year LC, 5-year PFS, and 5-year OS rates were 82.2, 84.1, and 79.0%, respectively, for AM patients receiving PORT after GTR, and they were 71.0, 71.9, and 81.5%, respectively, for those not receiving PORT after GTR. PORT could significantly improve 5-year LC rate (OR [95% Cl] = 2.59 [1.40–4.81], P = 0.002) and 5-year PFS rate (OR [95% Cl] = 1.99 [1.35–2.95], P = 0.001), but did not significantly improve 5-year OS rate (OR [95% Cl] = 1.07 [0.60–1.91], P = 0.828). Conclusion PORT could improve the 5-year LC rate and 5-year PFS rate in AM patients after GTR. AM patients might benefit from PORT after GTR.